2019
DOI: 10.1186/s40104-019-0370-5
|View full text |Cite
|
Sign up to set email alerts
|

GSTM3, but not IZUMO1, is a cryotolerance marker of boar sperm

Abstract: Background Cryopreservation is currently the most efficient method for long-term preservation of mammalian gametes and is extensively used in swine artificial insemination (AI) centres. However, it is well-known that cryopreservation procedures induce changes in the water phase in both intra and extracellular compartments, which alter the content and localisation of several proteins and ends up curtailing the structural integrity of functional sperm (i.e., cryoinjuries). Alterations and deficienci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
27
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 34 publications
3
27
2
Order By: Relevance
“…Since immunoblotting analysis found GSTM3 content to be reduced during semen storage, it becomes apparent that such enzyme is lost rather than relocalised from the mid-piece during liquid-storage. Contrary to the results of the present study, GSTM3 was reported to relocalise to the mid-piece following boar sperm cryopreservation [17].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Since immunoblotting analysis found GSTM3 content to be reduced during semen storage, it becomes apparent that such enzyme is lost rather than relocalised from the mid-piece during liquid-storage. Contrary to the results of the present study, GSTM3 was reported to relocalise to the mid-piece following boar sperm cryopreservation [17].…”
Section: Discussioncontrasting
confidence: 99%
“…Sperm GSTM3 was localised in the mid, principal, and end pieces of the tail and the equatorial subdomain of the head of samples at 0 h of liquid-storage. This localisation pattern is similar to that found in the boar [17] and other species, such as the buffalo [41]. Moreover, the localisation of GSTM3 in the sperm tail would contribute to explaining the dramatic effect of GSTs-inhibition upon sperm motility and mitochondrial function.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations